Configuring Pathways to Successful Rural Development: A Fuzzy-Set Qualitative Comparative Analysis of Korea’s Project in Kyrgyzstan - Choi, Young-Chool (Journal of Posthumanism, 2025)
This study applies Fuzzy-Set Qualitative Comparative Analysis (fsQCA) to identify key determinants influencing the outcomes of Korea's Integrated Rural Community Support Project in Kyrgyzstan. Conducted from 2021 to 2025 in 30 villages across the Osh and Batken regions, the analysis focuses on exploring the complex interactions of various factors—including community participation, infrastructure improvement, women's participation, income generation activities, and agricultural training—that affect the success of rural development initiatives. Utilizing fsQCA offers distinct methodological advantages, allowing for the assessment of conditions through their combinations rather than isolated effects, thus providing nuanced insights that traditional statistical methods might overlook. Results highlight those combinations involving high levels of community participation and infrastructure enhancement, particularly when integrated with women's participation or agricultural training, are significantly linked to successful project outcomes. The findings suggest that rural development interventions are most effective when adopting multidimensional, integrated approaches rather than single-factor solutions. Consequently, this study provides critical theoretical and practical implications for policymakers and development practitioners, advocating for comprehensive strategies tailored to local contexts. Future research could extend this analytical approach to other regions and incorporate additional socio-cultural, economic, and political dimensions, enhancing the broader applicability and impact of rural development projects internationally.